2011
DOI: 10.1111/j.1540-6210.2011.02412.x
|View full text |Cite
|
Sign up to set email alerts
|

Family‐Friendly Human Resource Policy: Is It Still Working in the Public Sector?

Abstract: Th e balance between work and family plays a pivotal but evolving role in human resource policy. Ensuring that human resource policy responds to rapidly changing American family demographics, particularly the recent sharp increase in single unmarried Americans, is a major challenge. Compensation policy long has focused on family-oriented values by promising increased capacity to provide for a family in exchange for higher work performance. Now, employees are voicing concerns about matters such as quality time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
81
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(88 citation statements)
references
References 33 publications
(68 reference statements)
3
81
2
2
Order By: Relevance
“…Kim and Wiggins (2011) also state the significant impact of traditional benefits on employee satisfaction and turnover intention. According to Social Exchange Theory (SET), traditional benefits can be regarded as positive and helpful activities demonstrated toward employees by the organization as these benefits generate obligations for employees to give back in positive and helpful ways.…”
Section: Benefits and Servicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Kim and Wiggins (2011) also state the significant impact of traditional benefits on employee satisfaction and turnover intention. According to Social Exchange Theory (SET), traditional benefits can be regarded as positive and helpful activities demonstrated toward employees by the organization as these benefits generate obligations for employees to give back in positive and helpful ways.…”
Section: Benefits and Servicesmentioning
confidence: 99%
“…Saltzstein, Ting, and Saltzstein (2001) family-friendly benefits and employees' job satisfaction. Besides, Lee and Hong (2011) and Kim and Wiggins (2011) indicate the positive impact of family-friendly benefits on work attitudes and performance. According to the perspective of SET, employees recognize these benefits as "extra."…”
Section: Benefits and Servicesmentioning
confidence: 99%
“…However, this can by achieved only if the employees have knowledge and skills necessary for effective work performance and its constant enhancement, which would maximise also their growth potential (Rastgoo, 2016;Razak et al, 2016;Lee, Bruvold, 2003). Kim and Wiggins (2011) points out that human resource policy must respond to rapidly changing demographics, concerning the current increase of single unmarried youngsters, turning into middleage employees and huge number of elderly people in agriculture, as it is a major challenge to work and satisfy needs of those differentiated groups. Furthermore, compensation policy has stagnated for a long time and has focused on family-oriented values by promising increased capacity to provide for a family in exchange for higher work performance.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…It is no longer sufficient and employees desire new ways to be treated (Rastgoo, 2016;Razak et al, 2016). Therefore, HR policy has to focus on shifting preferences of the employees aiming at other characteristics which differ widely by demographic characteristics (Kim and Wiggins, 2011).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…For instance, FFWP promotes organizational attachment by increasing organizational commitment, organizational citizenship behavior), and job satisfaction. In addition, some research has found that FFWP relate to a reduction in turnover intention (Kim & Wiggins, 2011) and improve organizational performance.…”
Section: Introductionmentioning
confidence: 99%